2005
DOI: 10.1182/blood-2005-01-0313
|View full text |Cite
|
Sign up to set email alerts
|

Both heterozygous and homozygous α+ thalassemias protect against severe and fatal Plasmodium falciparum malaria on the coast of Kenya

Abstract: Although the ␣ ؉ thalassemias almost certainly confer protection against death from malaria, this has not been formally documented. We have conducted a study involving 655 case patients with rigorously defined severe malaria and 648 controls, frequency matched on area of residence and ethnic group. The prevalence of both heterozygous and homozygous ␣ ؉ thalassemia was reduced in both case patients with severe malaria (ad-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
134
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 25 publications
11
134
3
1
Order By: Relevance
“…Another study in Ghana (Mockenhaupt et al, 2004) also found a large effect with a standardized OR value for α + thalassemia heterozygotes of 0.577. However, they did not observe an effect in homozygotes, a finding that Williams et al (2005a) suggested was due to low statistical power.…”
Section: Estimation Of Selection In Malarial Environmentsmentioning
confidence: 89%
See 4 more Smart Citations
“…Another study in Ghana (Mockenhaupt et al, 2004) also found a large effect with a standardized OR value for α + thalassemia heterozygotes of 0.577. However, they did not observe an effect in homozygotes, a finding that Williams et al (2005a) suggested was due to low statistical power.…”
Section: Estimation Of Selection In Malarial Environmentsmentioning
confidence: 89%
“…Recently, the deletional mutation rate for α globin (Lam & Jeffreys, 2006) and the amount of protection for α thalassemia genotypes in malarial environments have been estimated (Allen et al, 1997;Williams et al, 2005a). Here I use these values to examine the expected pattern of selection in nonmalarial environments and the dynamics of selection in malarial environments for α globin deletion variants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations